Design, fabrication and flight testing of a surveillance UAV - Idres, Moumen; Makame, Burhani; Ahmad, Bala Nabil; Naji, Saleh; Safiuddin, Ahmad (Trans Tech Publications, Switzerland, 2015)
Unmanned Aerial Vehicle (UAV) is becoming increasingly popular because it can perform variety of functions. These functions include surveillance, reconnaissance, monitoring, data collection and rescue operation. The purpose of this work is to design, fabricate and fly a low weight, low cost, small size UAV for a surveillance mission. The design is carried out based on Advanced Aircraft Analysis (AAA) software. The design process starts with the design specifications for a typical surveillance mission. Aircraft weight, wing loading and power loading were estimated in performance sizing process. Geometry was estimated using preliminary sizing. Aerodynamics of the aircraft was determined, which enabled the performance and stability to be analysed. If the desired performance is not achieved, the sizing is readjusted until a final design is reached. The aircraft was manufactured using foam, carbon rods, and fibreglass. The aircraft successfully flew at the first trial flight. This was followed by a successful flight with aerial photography